Penerapan Fire Safety Management Pada Bangunan Gedung Grand Slipi Tower Dikaitkan Dengan Pemenuhan Peraturan Dan Standar Teknis Proteksi Kebakaran - Effendie, Moch. Ichwan Nur (Universitas Suryakancana, 2017)
Abstract - Fire protection systems are basically consist of active fire protections which need energy (energized system), passive fire protection named as Built-in system, and Fire Safety Management (FSM), which is known as Human system. This thesis investigated the FSM aspect, since from many fire incidences, the main problems are often caused by less attention in applying this aspects. The research was focused on Grand Slipi Tower building, Jakarta where research variables comprises the influences of Human Systems, Equipment Systems and Standard Operating Procedures (SOP) either partially or simultaneously. To resolve this issues, a questionnaire was designed in respectively 15 questions for each variable. The questionnaire was distributed randomly to 55 respondents of 122 staff personels of Grand Slipi Tower. The responds of questionnaires resulted in scores for all variables that have been studied. To show the significance results of the simple regression, t-test was conducted and for multiple regression, F-test was conducted. The final results shows that Human System, Equipment System and SOP, either simultaneously or partially, affecting the compliances of fire protection codes and technical standards of the Grand Slipi Tower building with 99% data accuracy. The effect of Human System partially, in percent was 71,3%.Â The effect of Equipment System partially, in percent was 64.8%. The SOP effect in percent was 48.5%. While the effects of Human System, Equipment System and SOP simultaneously to the compliance of Fire regulations, codes and standards of the Grand Slipi Tower building in percent was 83.1%Keywords : Human System, Equipment System, SOP, fire protection regulations, codes and standards